Optical and electrical properties of conducting polythiophene/polyvinyl alcohol composites synthesized by gamma-ray irradiation method - A. Dandi, Aiman Moftah (2012)
Electrically conducting polythiophene (PTh) was prepared from 2-thiopheneacetyl chloride at different concentrations of 9.1, 16.7, 23.1, 28.6 and 33.3 wt% dispersed in polyvinyl alcohol (PVA) films. The sample films were irradiated in a γ-ray chamber at different doses of 0, 10, 20, 30, 40 and 50 kGy at ambient conditions. Upon gamma irradiation, the 2-thiopheneacetyl chloride monomer polymerized into conducting PTh by loosing H+ ions and formed conducting species of polarons. The SEM morphology of PTh/PVA composite of optimum 2-thiopheneacetyl chloride concentration and absorbed dose of 28.6 wt% and 30 kGy respectively, shows a good morphology with spherical size, 0.7 μm in diameter and spreaded uniformly in the PVA matrix. The UV-visible absorption peak of this PTh composite red-shifted to 400 nm and the intensity increases with increase of concentration and dose until the optimum values. The optical band gap energy Eg decreases with an increase of monomer concentration and absorbed dose. For examples, Eg decreased from 3.38 eV at 0 kGy to 3.19 eV at 30 kGy for 9.1 wt% and from 2.35 eV at 0 kGy to 2.15 eV at 30 kGy for 28.6 wt%. The impedance analyzer was used to determine the electrical conductivity and found that the conductivity increased with increase of monomer concentration and absorbed dose until they reached the optimum amounts. The direct current dc component is the major conductivity due to the formation of polarons in the PTh chain structure. For examples, the dc conductivity increased from 5.2×10-7 S/m at 0 kGy to 2.6×10-5 S/m at 30 kGy for 9.1 wt% and from 2.8×10-4 S/m at 0 kGy to 9.8×10-4 S/m at 30 kGy for 28.6 wt%.